The Emergence of Urbanization and Urbanism in Phenomenological Structural Sociology - Mocombe, Paul C. (International Journal of Criminology and Sociology, 2026)
Within Mocombe’s theories of phenomenological structuralism and consciousness field theory, this article outlines the emergence of the process of urbanization and urbanism as a way of life in the capitalist world-system. The paper connects, causally, the emergence of the latter with the formation of the former two, i.e., urbanization and urbanism, in the West.